Community Based Nutrition Education for Promoting Nutritional Status of Children under Three Years of Age in Rural Areas of Mahottari District of Nepal - Yadav, DK; Gupta, N; Shrestha, N; Kumar, A; Bose, DK (Journal of Nepal Paediatric Society, 2015)
Introduction: Maternal and child mortality have declined significantly in Nepal to the extent that Nepal is on track to meet the Millennium Development Goals for maternal and child mortality. Similar improvements have not been seen in general nutrition status of them. Objective of this study was to evaluate a nutrition-education intervention designed to improve nutritional status (reduce stunting, wasting and underweight) of children. Materials and Methods: It was an intervention with separate sample pretest posttest design. Two groups of Village Development Committee (VDC) from Mahottari district were recruited as interventional and control areas. The intervention was a 12-months nutrition education program and comprised of twelve times with 2-3 hour nutrition lectures and discussion classless conducted by the Female Community Health Volunteers (FCHVs). Results: The Present study found that number of underweight children increased by 7.6% in control group while it decreased by 17.7% in intervention group from baseline to endline in both groups. So, intervention programme was able to decrease the number of underweight children significantly. Study shows that wasting status of children increased by 11.4% in control group from baseline to endline period. While in intervention group wasting status of children decreased by more than 5% from baseline to endline period. Conclusion: Nutrition education intervention was effective to reduce wasting and underweight but did not reduce the stunting status of children. Stunting reflects failure to receive adequate nutrition over a long period of time and is affected by recurrent and chronic illness. Findings suggested that nutrition programme of longer duration should be implemented to control the stunting status of children. DOI: http://dx.doi.org/10.3126/jnps.v34i3.10286 J Nepal Paediatr Soc 2014;34(3):181-187